De Bonove lekcije za izboljšanje miselne učinkovitosti v kontekstu slovenskih osnovnih šol - Malešević, Tamara (Šolsko polje, 2007)
Edward de Bono says there are two facts about intelligence: one good and one bad. The bad one is that intelligence is mostly inherited and this is the reason it cannot be substantially increased. The good one is that thinking effectiveness is more important for living than (mostly) inherited intelligence. De Bono claims that thinking skills can be developed. Helping students to become THINKERS is one of the aims of De Bono's CoRT program. People think only because they do not have complete information. It is therefore sensible to improve thinking skills in order to compensate for the lack of information. We are going to use one of de Bono's techniques for focusing attention - PMI (plus, minus, interesting) - to introduce the effects of implementing De Bono's CoRT thinking lessons into our education system.
Keywords: kritično mišljenje; metodika; pouk; razmišljanje; učenje